Perspektif Pendidik dan Tenaga Kependidikan (PTK) di Kabupaten Blitar terkait Kepatuhan Protokol Kesehatan di Sekolah - Rahayenda Ivory Puryono; Anna Wahyuni Widayanti; Susi Ari Kristina (Universitas Gadjah Mada, 2023)
Educators and Education Personnel (EEP) are one of the priorities that take precedence in the stages of the vaccination program as a form of preventing the spread of COVID-19. In August 2022, there were cases of exposure to COVID-19 where the first program reached 86%, the cause was compliance with implementing health protocols. This study aims to determine the level of compliance in implementing the COVID-19 prevention health protocol and identify the factors that influence the level of compliance. This research is a quantitative non-experimental study with a cross-sectional study approach. Questionnaires were distributed to 522 EEP by purposive sampling, 339 EEP respondents were obtained with a response rate of 64.94%, divided into 290 EEP as research samples and 49 samples used for the reliability test. Data collection was carried out in September-November 2022 using an online questionnaire via the GoogleTM form. A reliable questionnaire was used with a Cronbach's α value 0.864. The results were tested of normality then analyzed by using the JAMOVI application. For parametric data, the student t-test was used, while for non-parametric data, Mann-Whitney and Kruskal-Wallis data were used. Spearman correlation is used to determine the factors that influence the level of EEP compliance. As results the level of EEP health protocol compliance was 67.9% in the medium category. Factors that influence the level of PTK compliance are the organizational environment (p-value 0.001) and self-efficacy (p-value 0.001). Meanwhile, the level of knowledge (p-value 0.093) showed no significant correlation on the level of EEP compliance.